2015
DOI: 10.1097/mjt.0b013e3182987983
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Monotherapy Is Usually Insufficient Treatment for Idiopathic Inflammatory Myopathy

Abstract: Idiopathic inflammatory myopathies (IIM) are a rare group of autoimmune diseases characterized by muscle inflammation. High-dose corticosteroids are conventionally used as the first-line therapy for IIM, but early introduction of noncorticosteroid immunosuppressive agents has become increasingly common in recent years despite a paucity of compelling evidence to support this. Here, we systematically analyze therapeutic practice patterns of IIM in a large municipal safety net medical center. We conducted a retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Nine patients were classified as amyopathic DM. The details of the PM and DM patients have already been described [10]. Four patients were classified as IBM and represent the primary cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Nine patients were classified as amyopathic DM. The details of the PM and DM patients have already been described [10]. Four patients were classified as IBM and represent the primary cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is considered a first-line drug, studies have shown that more than half of the patients fail to obtain a complete clinical response to CG in monotherapy and adding other immunosuppressive drugs in often necessary (B) [95,96].…”
Section: What Initial Dose Of Gc Should Be Used and For How Long In Pmentioning
confidence: 99%
“…In general, patients respond well to standard immunosuppressive therapies, such as glucocorticosteroids and intravenous immunoglobulins ( 5 7 ). However, a large number of patients are resistant to current therapies, and treatment of idiopathic inflammatory myopathies still remains a formidable challenge ( 8 ).…”
Section: Introductionmentioning
confidence: 99%